KRITIK DAN REINTERPRETASI TERHADAP AJARAN TRADISIONAL DALAM TEOLOGI FEMINIS KRISTEN - Sumiati Songlo'; Apriani Ratte, Immanuel Rombe Langi' (Adisam Publisher, 2023)
This research constitutes an in-depth literature review on the criticism and reinterpretation of traditional teachings within the context of Christian feminist theology. The primary focus of the study is to analyze how feminist theology creates critical space to evaluate patriarchal norms embedded in the interpretation of Christian religious doctrines. Through a comprehensive literature review, this research attempts to explore the contributions of various Christian feminist thinkers in reconstructing theological meanings involving women. The literature review method is employed to examine various feminist theological sources that encompass critiques of traditional religious narratives, theological concepts, and interpretations of sacred texts. In-depth analysis is conducted to understand how feminist theology reinterprets concepts such as the original sin, creation, and discourse about God, exploring ideas that empower women and advocate for gender equality. The results of this literature review analyze the role of feminist theology in bringing about changes in gender perceptions within Christianity. Critical thinking towards traditional interpretations opens opportunities for reforming religious practices, inclusivity in liturgy, and changes in church leadership. Furthermore, this research explores the impact of feminist theology on interpersonal relationships, social ethics, and women's participation in church ministries. By incorporating perspectives from various feminist theologians, this research provides profound insights into how criticism and reinterpretation of traditional teachings can pave the way for transformation in Christian theology. The implications of this study can provide a foundation for a more holistic and inclusive understanding of the role of women in religious contexts and ofler a basis for further discussions in formulating more equitable and just theological perspectives.